Avaliação do efeito dos polissacarídeos sulfatados extraídos da microalga Dunaliella tertiolecta como imunoestimulante em juvenis de camarão Litopenaeus vannamei - Moreira, Renato Teixeira (2010)
Aquaculture is one of the activities that most expands around the world and microalgae such as shrimps cultures have a great contribution into this progress. The aim of this study was the culture of the marine microlgae Dunaliella tertiolecta and extract its sulfated polysaccharides from the biomass and from the culture medium as well as to evaluate the effects of polysaccharides administration directly into the cultivation water of Litopenaeus vannamei shrimp’s post-larvae and juveniles. During microalgae cultivation some growth parameters and culture development were evaluated, and the sulphated polysaccharides were extracted from biomass and the culture medium. These polysaccharides were directly administrated into the water, in the concentration of 0.5; 1.0 and 2.0 mg L-1 to pl’s of L. vannamei, wich were submitted to a saline stress often applied to verify the quality of pl’s in the most of shrimps farms. The juveniles were exposed to the same concentration of the polysaccharides in a five days period in laboratory conditions. Then, we collected the animals haemolymph to analyze some hematoimmunological parameters, like total haemocyte count (THC), phenoloxidase enzime activity (PO), haemolymph aglutination capacity and total protein concentration. The results showed an excelent development of the microalgae D. tertiolecta, reaching a maximum yield of 6.67 g L-1 in dry biomass and in 10 L of culture medium, from wich were obtained 2.3 g of gross sulphated polysaccharides. The pl’s presented high resistance to the saline stress, when submitted to a 0.5 mg L-1 concentration of PS, and at the end of the test only 12.5% of individuals died, while in the juveniles the lower accumulated mortality was 6.7% when the higher dosage of PS was administrated. The analysis of the immunoparameters did not show any variation except the haemocyte total count and haemolymph protein concentration, wich were significantly reduced within the increase of polysaccharides dosage in the water. Future histological studies can be an alternative to reveal the possible haemocytes migration to the animals gills exposed to higher polysaccharides concentration in the water